2006
DOI: 10.1002/polb.20737
|View full text |Cite
|
Sign up to set email alerts
|

Control of diameter, morphology, and structure of PVDF nanofiber fabricated by electrospray deposition

Abstract: Poly(vinylidene fluoride) (PVDF) nanofibers were prepared by electrospray deposition (ESD). To control the diameter, morphology, and structure of PVDF nanofibers, some parameters were investigated, such as polymer concentration, nozzle‐to‐ground collector distance, feeding rate of the polymer solution, and applied voltage. The fabricated fiber was 80–700 nm in diameter. The increase in the polymer concentration caused an increase in the polymer viscosity and fiber diameter. At low polymer concentration (5 wt %… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
100
1
2

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 121 publications
(108 citation statements)
references
References 25 publications
5
100
1
2
Order By: Relevance
“…Our measurement has shown at 10 kV, that the measured extraction rate is about 0.8 ml/h, which increases to 1 ml/h at 20 kV and 3 ml/h at 30 kV. Although our voltage-dependent results are generally in good agreement with the literature [19,20,38] , several inconsistent results have also been reported. For instance, Katti et al [17] reported that an increase in voltage caused a decrease in nanofiber diameter initially, and further increase in the voltage caused fluctuation of the nanofiber diameter.…”
Section: Effect Of Applied Biassupporting
confidence: 54%
See 2 more Smart Citations
“…Our measurement has shown at 10 kV, that the measured extraction rate is about 0.8 ml/h, which increases to 1 ml/h at 20 kV and 3 ml/h at 30 kV. Although our voltage-dependent results are generally in good agreement with the literature [19,20,38] , several inconsistent results have also been reported. For instance, Katti et al [17] reported that an increase in voltage caused a decrease in nanofiber diameter initially, and further increase in the voltage caused fluctuation of the nanofiber diameter.…”
Section: Effect Of Applied Biassupporting
confidence: 54%
“…More controversially, measurement taken by Gu et al [21] showed no correlation between fiber diameter and bias voltage. Moreover, careful inspection of the data reported by Zhang et al [19] and Nasir et al [20] also revealed a sublinear curvature, whereas our results show a superlinear curvature. Such a complex spectrum of the voltage-dependent results should be thoroughly analyzed, in order to obtain a comprehensive understanding of the whole picture, although it is worth mentioning that most of these reported results are obtained using flow control.…”
Section: Effect Of Applied Biascontrasting
confidence: 51%
See 1 more Smart Citation
“…Several other studies were recently published on electrospinning PVDF fibers, Harisson et al 37,38 , Zhao et al 39 , Nasir et al 40 , Re and Dzenis 41 , Yee et al…”
Section: Electrospun Of Pvdf Fiber Matsmentioning
confidence: 99%
“…8 Most of approaches for introducing porous structure into the bulk on a nanofiber relied on (i) the ESD of blends or composite followed by selective removal of one component, 9,10 and (ii) phase separation based on evaporation of solvent or in the presence of vapor during ESD. 11,12 Here, we attempt to prepare porous polymeric nanofiber from polymer blend by using a former approach.…”
mentioning
confidence: 99%